Impact of Climate Change on Wildlife health: A Manager's Perspective - Awadhiya, Ankur (Indian Forester, 2018)
All over the world today, wildlife is reeling under a constant threat of extinction through the impacts of changing climate. This extinction will probably be caused by the overwhelming impact of climate on the health and welfare of wildlife. In this paper a conceptual review of the existent situation and the strategies available to wildlife managers to conserve wildlife under these changing circumstances is offered. The Author explore the components of climate and discuss how the changes in climate are impacting the health of our wildlife. The twin strategies of climate change mitigation and adaptation, and how these can be adapted for deployment to the management of health and welfare of wildlife are analysed. These strategies are imperative to help abate the detrimental outcomes of climate change on wildlife, and require an urgent attention of managers without delay.